STRUCTURE OF COMPLEX SENTENCES IN UZBEK: A CORPUS-BASED SYNTACTIC ANALYSIS - Iroda Jurayeva; Shaxzoda NORMAMATOVA (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  In  this  article,  the  structure  of  complex  sentences  in  the  Uzbek language is analyzed syntactically based on corpus linguistics. The study examines structural models, types of complex sentences (compound, complex, and asyndetic), connective devices, and semantic-logical relations using a corpus compiled from texts of various stylistic layers of modern Uzbek.